Sinergi Mahasiswa dan Warga dalam Gerakan Bersih Lingkungan Kelurahan Kalia-Lia - Nastia, Nastia; Astuti, Fina (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Environmental cleanliness is very important for creating healthy and sustainable living spaces. However, due to low public awareness and a lack of collaboration between residents and outside parties, there are still waste management issues in Kalia-lia Village that have not been properly addressed. Through a collaborative movement between students and local residents, this community service program (PKM) aims to increase public awareness and participation in maintaining environmental cleanliness. The activities include educating the community on the importance of cleanliness, conducting joint efforts to clean up the environment, and forming the “Friends of the Kalia-lia Environment” group to support the sustainability of these activities. The results of the activity show that good communication and cooperation have been established between students and residents, and participation in environmental clean-up activities has increased. It is hoped that this synergy will become a model for sustainable cooperation to create a healthy and clean environment in Kalia-lia Village.